PENGARUH PUBLIC SERVICE MOTIVATION (PSM), ORGANIZATION CITIZEN BEHAVIOR (OCB) DAN KOMPETENSI TERHADAP KINERJA PERANGKAT DESA KECAMATAN SIAK KECIL - Saputra, Billy Yanis; Fakhruddin, Imam; Firdaus (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
This research is motivated by the low assessment given by the community on the performance of village officials. This research is a quantitative study with an associative approach that aims to analyze the effect of public service motivation, organizational citizen behavior and competence on the performance of village officials. Hypothesis testing in this study uses multiple linear regression analysis methods using SPSS version 26.0 as a test tool. The results showed that public service motivation and organization citizen behavior had a positive and significant effect on the performance of village officials. In government organizations there is a motivation to serve the public. This motivation encourages them to choose the public sector as a place to devote their efforts and energy.